If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(u + 9) = -40 Reorder the terms: -8(9 + u) = -40 (9 * -8 + u * -8) = -40 (-72 + -8u) = -40 Solving -72 + -8u = -40 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + -8u = -40 + 72 Combine like terms: -72 + 72 = 0 0 + -8u = -40 + 72 -8u = -40 + 72 Combine like terms: -40 + 72 = 32 -8u = 32 Divide each side by '-8'. u = -4 Simplifying u = -4
| 2+3(x+15)=37 | | 3x^4+5v^2=2 | | C+7.16=9.01 | | y=x^2-24+5 | | 7(3c+6)-3b-5c=14 | | 4(b-5)=2(4b+5) | | 3y-7=-y-3 | | Y-.4=.1 | | 7+q=5+2q | | x-2(x+3)=2x-3(x+12) | | 12y-3y+6=15 | | 0.3a=a | | -12-x-3=15-18+9 | | 8x^2+65x+8= | | -3(6+4x)=92 | | 5x^2-16x-16=y | | .51+t=1.00 | | -6x^2-600= | | x+127=180 | | -9=s+-4 | | y=x^2-24x+5 | | x^5-9x^3=0 | | 11-x=5 | | 2(x+3)-3x=5-x-11 | | 7.08x^6+4.303x^3=9.6 | | 9=x/2+1 | | 3x=8y | | -5=-3-n | | a-3c=6 | | 15x^2-19x+6= | | 9x^2-22x^2=0 | | 24s-53=39-s |